IL-4/JAK/STAT6 pathway activation in follicle center lymphoma of the lower female genital tract: A case report - Kitaoka, Takumi; Satou, Akira; Kitamura, Eiichi; Aizawa, Keiko; Sudo, Takeshi; Abe, Madoka; Kabasawa, Takanobu; Suzuki, Kazushi; Uchiyama, Naoya; Ohe, Rintaro (Human Pathology Reports, 2025)
Follicle center lymphoma (FCL) of the lower female genital tract (LFGT) is a recently proposed subtype of B-cell lymphoma that resembles primary cutaneous follicle center lymphoma. Although targeted next-generation sequencing (NGS) studies have identified recurrent TNFRSF14 mutations in FCL of the LFGT, its broader mutational landscape remains largely uncharacterized. We report a case of FCL of the LFGT in a woman in her 40s presenting with a cervical tumor. Histological examination revealed a predominantly diffuse proliferation of CD20+, CD79a+, BCL6+, HGAL+, CD23+, and BCL2− atypical lymphocytes, consistent with a centrocytic phenotype. Numerous T follicular helper cells were observed in the background of the lesion. Whole-exome sequencing identified 1,336 coding variants. After filtering based on tumor cell content and CADD phred score (≥20), 125 variants were retained, including a nonsense mutation in TNFRSF14 and missense mutations in IL4R and SOCS3. The TNFRSF14 mutation may contribute to the accumulation and activation of T follicular helper cells by disrupting the inhibitory HVEM–BTLA signaling pathway. In addition, IL4R and SOCS3 mutations may lead to upregulation of the IL-4/JAK/STAT6 pathway, promoting tumor cell survival and proliferation. These findings provide new insights into the molecular pathogenesis of FCL of the LFGT.